SER MÃE/MULHER EM FAMÍLIAS MONOPARENTAIS: UMA DISCUSSÃO INTERSECCIONAL DE CLASSE, RAÇA E GÊNERO - RICKLI, JESSYKA LOPES (2023)
This thesis aimed to characterize the phenomenon of female single parenthood, according to the intersections of class, race and gender. We intend to understand this problem from the intersectional perspective. It is considered that these discussions can contribute to thinking about female single parenthood in a heterogeneous way, highlighting the particularities experienced by women/mothers who take care of their children alone. The development of this research begins with changes in family arrangements, with a historical discussion that starts from the bourgeois nuclear model, until it reaches new family configurations, highlighting female single-parent families. As a basis for this research, a bibliographical survey was carried out, aiming to identify the concepts developed by the Brazilian scientific academy on the phenomenon of female single parenthood, using dissertations and theses with a temporal cut from the years 2000 to 2020, being able, in this way, to contextualize about the discourse produced in the face of this phenomenon, so that we can return to the local scope and hear the stories of women/mothers in single-parent families. The research methodology is based on a qualitative research, with data collection, based on the theories and techniques of Oral History, thus allowing the visualization of the experiences lived in the daily life of female single-parent families. In this way, twelve interviews were carried out with a variety of women/mothers, highlighting the subjectivities in occupying this place. The analyzes of the interviews were divided into three categories: meaning of motherhood, paternal responsibility and support networks. Based on the bibliographical analyzes and the interviews carried out, one can see the difficulties in occupying this place, surrounded by feelings of exhaustion, abandonment, overload, but also feelings of well-being and accomplishment, experiences that are crossed by different social inequalities. The interviewees' reports corroborate the prerogatives of gender roles, in which motherhood is destined only to women, who, in most cases, are solely responsible for caring for their children.